Eight to thirteen years old children fear at dental treatment - Aryani, Dwi Destaria; Gartika, Meirina; Hidayat, Syarief (Padjadjaran Journal of Dentistry, 2013)
Introduction: Fear is an emotion occurring in situation of stress and uncertainty and can make the person experience the threatened or helpless feeling. The etiology of child dental fear consist of personal factor, external factor, and dental factor. The purpose of this study was to describe the child fear at 8-13 years of age toward dental treatment and find the most dominant etiology of fear. Methods: A descriptive survey was conducted amongs 53 childs in MI Cikapayang Islamic Elementary School who had ever gotten the dental treatment using CFSS-DS and questionnaire. The sampling method was total sampling. Results: The result shows that the description of child fear at 8-13 years of age to the dental treatment is not afraid at all (45,3%), a little afraid (33%), a fair amount afraid (15,2%), pretty much afraid (4%), and the most little is very afraid (2,5%). The etiology of child dental fear consist of personal factor (52,8%), external factor (7,5%), and dental factor (39,6%). Conclusion: Majority of child fear at 8-13 years of age to the dental treatment in MI Cikapayang Islamic Elementary School feel not afraid at all to the dental treatment (45,3%) and the most dominant etiology is personal factor (52,8%).